Heidegger's phenomenology of perception learning to see and hear hermeneutically. - Kleinberg-Levin, David Michael, 1939- (New Heidegger research., 2021)
This second volume of David Kleinberg-Levin's study of Heidegger's phenomenology of perception sheds light on how Heidegger works, both critically and constructively, with seeing and hearing. The author explores how these capacities address the ills illuminated by Heidegger's critique of metaphysics and the nihilism devastating the Western world.